2014
DOI: 10.1080/00324728.2014.889741
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socio-economic status on net fertility during the historical fertility decline: A comparative analysis of Canada, Iceland, Sweden, Norway, and the USA

Abstract: Most previous work on the historical fertility transition has been macro-oriented, using aggregate data to examine economic correlates of demographic behaviour at regional or national levels, while much less has been done using micro data, and specifically looking at behavioural differentials among social groups. In this paper we study at the impact of socioeconomic status on net fertility during the fertility transition in five Northern American and European Countries (Canada, Iceland, Norway, Sweden and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 45 publications
5
43
0
3
Order By: Relevance
“…For example, the 10 % to 15 % higher marital fertility rates among women married to farmers relative to women married to men with professional, managerial, and sales occupations were approximately one-half of those observed in a recent analysis of the 1900 IPUMS sample (Dribe et al 2014a). The observed 8 % to 22 % higher marital fertility rates among Irish-, German-, and British-born couples relative to native-born couples were also about one-half of the differences observed in an analysis of the 1910 census (Morgan et al 1994).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…For example, the 10 % to 15 % higher marital fertility rates among women married to farmers relative to women married to men with professional, managerial, and sales occupations were approximately one-half of those observed in a recent analysis of the 1900 IPUMS sample (Dribe et al 2014a). The observed 8 % to 22 % higher marital fertility rates among Irish-, German-, and British-born couples relative to native-born couples were also about one-half of the differences observed in an analysis of the 1910 census (Morgan et al 1994).…”
Section: Discussionmentioning
confidence: 72%
“…Although evidence is limited, most investigators of the North American and European fertility declines have assumed that fertility was positively correlated with income, wealth, and socioeconomic status prior to the onset of the fertility transition (e.g., McInnis 1977; Steckel 1985) and negatively correlated after its onset (e.g., Becker and Lewis 1973), suggesting diverse and changing quantity-quality tradeoffs (Dribe et al 2014a). Evidence on when and how the income/wealth and fertility relationship changed in the United States is mixed.…”
Section: Prior Researchmentioning
confidence: 99%
“…There is a widespread view in the literature that higher social status was associated with high fertility in pre-transitional populations, but that this situation reversed during, or even well before, the transition began (e.g., Livi-Bacci 1986; Skirbekk 2008; Clark and Cummins 2015). This change has been explained by the higher social groups acting as forerunners to the decline (Haines 1989a, 1992; Dribe et al 2014a). However, these generalizations are based on rather thin empirical grounds.…”
Section: Introductionmentioning
confidence: 99%
“…Dribe et al 2014;Edin and Hutchinson 1935;Skirbekk 2008;Westoff 1954). Overall, research have found how a pre-industrial pattern of a positive gradient between SES and fertility transformed into a negative pattern after the industrial revolution, though this pattern is complicated in the past, and recently there is evidence of a reemergence of a partial positive association in contexts such as contemporary Sweden.…”
Section: Prior Literature On Socioeconomic Status and Its Relationshimentioning
confidence: 99%
“…This shift towards investing in children, intentional or not, is an impetus both for further income growth and for social mobility. The degree to which the new fertility behavior is adopted can be important to explain the trajectory of families, not least due to socioeconomic differences in the adoption of low fertility (Dribe et al 2014;Livi-Bacci 1986), and since fertility behavior also is correlated across generations (Anderton et al 1987).…”
Section: The Socioeconomic and Demographic Transformations Of The 19 mentioning
confidence: 99%